Analisis Penerapan Manajemen Sumber Daya Manusia dalam Meningkatkan Mutu Pendidikan di SMA Muslimin Sindangkerta - Huda, Iqbal Saepul; Maryono, Dicky (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This study aims to determine the application of human resource management in improving the quality of education at SMA Muslimin Sindangkerta. This type of research uses descriptive research using a qualitative approach. The data collection method used in this study is by conducting observations, interviews, and documentation. The results of this study are that the application of human resource management in improving the quality of education at SMA Muslimin Sindangkerta can include several stages including: 1). needs and information analysis, 2). teacher/employee recruitment, 3). employee induction, 4). teacher placement, 5). granting authority and responsibility, 6). implementation of supervision of employee performance, 7). career development, 8). termination of employment and 9). Provision of severance pay. While the supporting factors are 1). The existence of programs run by the school, 2). The existence of facilities and infrastructure that maximize the learning process, 3). The principal has many considerations and 4). There is an evaluation.